Changes in intermuscular connectivity during active elbow extension reveal a functional simplification of motor control after stroke - Delcamp, Célia; Cormier, Camille; Chalard, Alexandre; Amarantini, David; Gasq, David (Frontiers in Neuroscience, 2022)
Background: Stroke alters muscle co-activation and notably leads to exaggerated antagonist co-contraction responsible for impaired motor function. However, the mechanisms underlying this exaggerated antagonist co-contraction remain unclear. To fill this gap, the analysis of oscillatory synchronicity in electromyographic signals from synergistic muscles, also called intermuscular coherence, was a relevant tool. Objective: This study compares functional intermuscular connectivity between muscle-pairs of the paretic and non-paretic upper limbs of stroke subjects and dominant limb of control subjects, concomitantly between two muscle pairs with different functional role, through an intermuscular coherence analysis. Methods: Twenty-four chronic stroke subjects and twenty-four healthy control subjects were included. Subjects performed twenty elbow extensions while kinematic data and electromyographic activity of both flexor and extensor elbow muscles were recorded. Concomitantly to the assessment of antagonist co-contraction, intermuscular coherence was analyzed in the beta frequency band. Results: Intermuscular coherence was higher in the stroke subjects’ paretic limb compared to control subjects. For stroke subjects, the intermuscular coherence of the antagonist-antagonist muscle pair (biceps brachii – brachioradialis) was higher than that of the agonist-antagonist muscle pair (triceps brachii – brachioradialis). For the paretic limb, intermuscular coherence of the antagonist-antagonist muscle pair presented a negative relationship with antagonist co-contraction. Conclusions: Differences in intermuscular coherence between the paretic limb of stroke subjects and the control subjects suggest a higher common central drive during movement. Furthermore, results highlight the association of stroke-related alteration of the intermuscular functional connectivity and the alteration of the motor function.